2023
DOI: 10.1111/nrm.12368
|View full text |Cite|
|
Sign up to set email alerts
|

Object‐based image analysis (OBIA)‐based gully erosion dynamics, sediment loading rate and sediment yield study in Lake Hawassa Sub‐basin, Ethiopia

Abstract: Gully erosion is a serious environmental issue in Lake Hawassa Sub‐basin. It has affected a large portion of the catchment, and a large amount of sediment has been transported into the lake. This condition needs to be addressed. However, before conservation techniques are implemented, the gully systems should be mapped, their extent and changes over time need to be measured, and their capacity to produce sediment from their catchments should be determined. The objective of this study were, therefore, to map an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Nash-Sutcliffe E ciency Coefficie Model calibration period (1)(2)(3)(4)(5)(6) 13.248 0.997 0.994 Model validation period (7)(8)(9)(10)(11)(12)(13) 43.876 0.958 0.958…”
Section: Relative Error Correlation Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Nash-Sutcliffe E ciency Coefficie Model calibration period (1)(2)(3)(4)(5)(6) 13.248 0.997 0.994 Model validation period (7)(8)(9)(10)(11)(12)(13) 43.876 0.958 0.958…”
Section: Relative Error Correlation Coefficientmentioning
confidence: 99%
“…Gully erosion has attracted increasing attention from scientists, and gully development leads to loss of crop yields and available land, as well as an increase in farmers' tillage workload. Studies have shown that gully erosion is often the primary sediment source [9][10][11][12]. Gully erosion has long been neglected because it is challenging to study and predict [13].…”
Section: Introductionmentioning
confidence: 99%